Single cell and immunity: Better understanding immune cell heterogeneities with single‐cell sequencing - Dongsheng Chen; Yonglun Luo; Genhong Cheng (Wiley, 2022)
Abstract Single‐cell sequencing has scientific impacts on better understanding immunity. There is rapid development in single cell‐based databases and analytic tools to provide the potential for clinical and translational discovery. The understanding of single‐cell‐based immunity needs a strong program and solid evidence of preclinical and clinical validation and evaluation. The current special topic issue on single cell and immunity aimed to provide strong communication for the progress of single‐cell‐based studies on immune cell functional diversity in development and disease. The topic has a clear scope on the application of single‐cell sequencing to better understand immune cell heterogeneities, functions, cell‐cell interactions, responses and regulatory roles in systems immunology and diseases.